STUDI HADIS DI KALANGAN ORIENTALISME - Aan Supian (Universitas Islam Negeri Fatmawati Sukarno, 2016)
Orientalism was originally conceived as an ideology or thought alliran undertaken by Western scholars to the development and progress of East countries, both from the aspect of religion, language, culture, history and other aspects. Later, some experts said that a study conducted by Western scholars of the East, primarily related to the Arab and Islamic world. One of the studies in the field of Islam is the Hadith. Some Orientalists much consern in Hadith studies, among others, Ignaz Goldziher and Joseph Schacht. Among the views Goldziher about tradition is that most traditions can not be trusted as a whole as a source of teachings originating from the Prophet. Most of the material hadith in the collections of hadith originating from the development of the religious, social and historical Islam is derived from the characters in the first two centuries of tradition (century I and II H). It is similar, even more extreme, Joseph Schacht argued that the traditions that were collected in the book of hadith basically sourced from the Successors (formula scholars centuries II and III H), no one hadist authentic sources of the Prophet, especially the traditions about their law problem